Daily wisdom for why does he do that? eaudiobook Encouragement for women involved with angry and controlling men. - Bancroft, Lundy (Tantor Media, 2015)
Even if you've read Why Does He Do That? , it may be hard to see the truth of what is happening to you. You may feel overwhelmed by confusion, loss, and fear, and find yourself looking away from the truth and falling back into traumatic patterns. Like a constant friend, this collection of meditations is a source of strength and reassurance designed to speak to women like you, women in relationships with angry and controlling men. It helps you to digest what is happening a piece at a time, so that you can gain clarity, safety, and freedom. To learn to value and respect yourself—even when your partner makes it very clear that he does not—each day centers on one of seven themes designed to empower, encourage, and inspire you . . .